NuGet 2 essentials take advantage of the NuGet package manager, both as a consumer and a publisher of .NET class libraries - Arh, Damir; Daki(acute)c, Dejean; Safari eBooks (Birmingham, UK : Packt Pub., 2013)
"This book is intended for .NET developers who want to learn more about NuGet. Although it doesn't require any prior knowledge about NuGet itself, it requires familiarity with Visual Studio and the .NET Framework. All the code in the examples are written using C#; therefore, basic knowledge of the language is required as well."--Preface.
Description based on online resource; title from cover (Safari, viewed Feb. 6, 2014).
Includes index.
Keywords: Microsoft .NET Framework; Database management; Electronic books